Ingeborg Bachmanns «Das Buch Franza»: Rekonstruktion der örtlichen Topoi - Isapchuk, Yulia; Isapchuk, Yulia (Philosophicae Universitatis Ostraviensis, 2024)
The study examines the uncompleted novel ,The Book of Franzaʻ (,Das Buch Franzaʻ, 1965–1966) written by the Austrian writer Ingeborg Bachmann. The attention is focused on the specifics of the topographical paradigms „center“ and „province“, categories „fictional“ and „real“, which form dichotomous pairs and reconstruct the space. The article investigates three main topoi, which, at the level of form, correspond to three chapters of ,The Book of Franzaʻ. The chapter ,Return to Galicienʻ presents the Carinthian province, ,Jordanian timeʻ – the Austrian post-war metropolis and ,The Egyptian darknessʻ – the desert of North Africa that balances the space specifics of the text.
Keywords: Інґеборґ Бахман, «Книжка Франци», топос, центр, провінція; Інґеборґ Бахман, «Книжка Франци», топос, центр, провінція